Protocolo para selecionar alternativas de produtos para instalações provisórias de canteiro de obras - Zeule, Ludimilla de Oliveira (Universidade Federal de São Carlos, 2018)
Sustainability is a topic widely addressed in the various sectors of civil construction. In the building sector, sustainable practices have been gaining great interest both in the field of research and development of new technologies aimed at products, and in practical applications at construction sites. The performance of the Provisional Construction Site Installations (IPC) is a current and important topic, since most works are not concerned with the proper selection of materials for these facilities, compromising their safe and functional use, in addition to great losses to the users of these constructions, which are temporary, but house workers for nine or more hours of workday. Traditionally, civil construction has problems with decision-making processes, especially with regard to the lack of criteria for selecting materials. Thus, this study proposes the use of a decision-making method - Choosing by Advantage (CBA) to select product alternatives that impact less from the point of view of sustainability. As an analysis, a widely used component was adopted, which are lightweight roofs (with five different tiles) and modular container systems (with three different options) used as IPC. The method of this research proposes the design of a simplified protocol to be followed in order to obtain an analysis on the best type of tile and containers among those analyzed, according to the parameters identified as necessary to be used in the temporary installations of construction sites. This research assesses the applicability of the Multiple-Criteria Decision-Making (MCDM) methodology in helping construction site planning and design teams to choose more sustainable alternatives to IPC. Therefore, the CBA decision-making method has demonstrated that it meets the sustainability aspects and facilitates the comparison of alternatives according to the factors chosen. In general, it is expected that this work will collaborate to expand knowledge about decision-making methods in the construction sector, also helping to disseminate sustainability according to a systemic view and based on technical information.
Protocol for selecting alternative products for temporary construction site installations
Keywords: Sustentabilidade; Construção civil; Método de tomada de decisão; Coberturas leves; Contêineres; Instalações Provisórias do Canteiro de Obras; Sustainability; Multiple-Criteria Decision-Making; Lightweight cover (tiles); Container; Provisional Installations of Construction Site; Choosing by Advantage; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL